The Influence of Intellectual Capital and Audit Committee on Financial Performance of Banking Companies on IDX - Qintharah, Yuha Nadhirah; Bagaskara, David Nando (Universitas Mercu Buana, 2021)
The purpose of this study is to determine the influence of Intellectual Capital and the Audit Committee on the Company's performance in banks listed on the Indonesia Stock Exchange and how much influence the Intellectual Capital and the Audit Committee both partially and simultaneously have on the Company's performance in banks listed on the Indonesia Stock Exchange. The research method used in this study uses quantitative methods. Respondents in this study were banking sector companies listed on the IDX which published financial statements in a row for 3 years from 2017-2019 with a sample of 39 companies and the data collection method used Purposive Sampling, namely taking the necessary samples using the criteria specified. has been determined by the researcher. The results obtained from this study are Intellectual Capital and the Audit Committee have no effect on the Company's performance simultaneously or simultaneously and the results also show that individually the Intellectual Capital variable has no effect on the Company's Performance and the Audit Committee variable produces the same thing that there is no influence to the Company's Performance.